2021
DOI: 10.1128/iai.00680-20
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 Attenuates Neutrophil Migration and IL-6 Expression through Fpr2 in a Mouse Model of Streptococcus suis-Induced Meningitis

Abstract: Streptococcus suis (S. suis) serotype 2 is a crucial pathogenic cause of bacterial meningitis, a life-threatening disease with neurological sequelae and high rates of mortality. Inflammation triggered by S. suis infection must be precisely regulated to prevent further tissue damage. As a glucocorticoid anti-inflammatory mediator, Annexin A1 (AnxA1) mainly acts through formyl peptide receptor 2 (Fpr2) to alleviate inflammation in the peripheral system. In this research, we evaluated the roles of AnxA1 and Fpr2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Studies on mouse models of bacterial meningitis revealed a stronger glial cell marker expression in FPR1-deficient mice and an increase of activated microglial cells and neutrophil infiltration in FPR1- or FPR2-deficient mice, thus suggesting that FPRs exert an important role in the immune responses within the CNS and that the lack of these receptors leads to a dysregulation of the inflammatory response compared with wild-type mice. In this context, these researchers have observed that the proinflammatory reactions in FPR1 and FPR2 deficient cells resulted significantly increased [ 10 , 45 ]. Moreover, it has been demonstrated that FPRs play a major role in crotoxin anti-inflammatory activities that are inhibited by the pretreatment with Boc2, a selective antagonist of FPRs [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mouse models of bacterial meningitis revealed a stronger glial cell marker expression in FPR1-deficient mice and an increase of activated microglial cells and neutrophil infiltration in FPR1- or FPR2-deficient mice, thus suggesting that FPRs exert an important role in the immune responses within the CNS and that the lack of these receptors leads to a dysregulation of the inflammatory response compared with wild-type mice. In this context, these researchers have observed that the proinflammatory reactions in FPR1 and FPR2 deficient cells resulted significantly increased [ 10 , 45 ]. Moreover, it has been demonstrated that FPRs play a major role in crotoxin anti-inflammatory activities that are inhibited by the pretreatment with Boc2, a selective antagonist of FPRs [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study using a mouse model of Streptococcus suis -induced meningitis, indicated that AnxA1 exerted anti-inflammatory effects via attenuating leukocyte infiltration, inflammatory mediator production, and astrocyte or microglial activation in the brain, along with decreasing neutrophil adherence to the endothelium through FPR2, thus inhibiting meningitis progression. Significantly, the study also revealed that AnxA1 decreases IL-6 expression and effect through the FPR2/p38/COX-2 pathway ( Ni et al, 2021 ). These data highlight the potential therapeutic use of AnxA1 in bacterial meningitis.…”
Section: Role Of Formyl Peptide Receptor In Neurological Disease Via Regulation Of Inflammationmentioning
confidence: 95%
“…Among the 46 articles studying in vitro activation of neutrophils by S. suis, only 13 studies (28%) measured neutrophil purity after isolation [44,45,54,62,[69][70][71][72][73][74][75][76][77] (Figure 3). A diversity of methods were used to assess cell purity: Giemsa/Wright's stain [44,73,74], Hoechst stain (microscopy) [71,72] or flow cytometry using different markers (for exam-ple, Ly6G+, CD11b+) [54,[75][76][77]. However, in these studies, the purity was comprised between 75% and 97% and the high risk of contaminating cells probably compromised the interpretation of the results when the purity was low.…”
Section: Purity and Viability Of Neutrophils 231 Isolation Methods An...mentioning
confidence: 99%